Dental patient knowledge about the effects of smoking and attitudes about the role of dentists in smoking cessation - Yahya, Nurul Asyikin; Saub, Roslan; Md Nor, Mariani; Yusoff, Noriah (Seameo Regional Tropical Medicine & Public Health, 2017)
Dentists can offer their patients who smoke tobacco assistance with smoking cessation. We conducted this study to assess dental patient knowledge about the effects of smoking and perceptions and attitudes regarding the role of dentists in smoking cessation counselling. We conducted this study to inform tobacco cessation programs that could potentially include dentists. We conducted a cross-sectional study using a self-administered questionnaire among 375 patients. The mean age of subjects was 33.4 years; females comprised 51.5%. Participants were divided into 3 groups: those who never smoked (n = 263, 70.7%), smokers (n = 92, 24.7%), and ex-smokers (n = 17, 4.5%). Significantly more participants (p = 0.046) who never smoked (92.9%) knew smoking can cause bad breath than smokers (86.9%). Significantly more participants (p = 0.002) who never smoked (74.8%) knew smoking can cause periodontal disease than smokers (57.6%). Significantly more participants (p < 0.001) who never smoked (84.5%) knew smoking can cause oral cancer than smokers (66.7%). Significantly more participants (p < 0.001) who never smoked (86.7%) knew smoking can cause lung cancer than smokers (69.7%). Significantly more participants who never smoked (85.5%) felt dentists should be interested in the smoking status of their patients (p = 0.004) than smokers (72.6%). Significantly more participants (p = 0.08) who never smoked (69.6%) stated dentists should give smoking cessation advice than smokers/ex-smokers (59.0%). Smoker/ex-smokers had less knowledge about the effects of smoking on oral and general health than non-smokers. Both smokers/ex-smokers and non-smokers felt dentists should provide smoking cessation advice.